Nanoporous electrode with stable polydimethylsiloxane coating for direct electrochemical analysis of bisphenol A in complex wine media. (30th March 2023) - Wang, Jingjing; Yu, Jiening; Yu, Yuan; Luo, Zisheng; Li, Gangfeng; Lin, Xingyu
Highlights: An innovative electrode design for direct electrochemical analysis in wine samples. Facile contact heating for grafting an ultrathin PDMS layer on electrode surface. Direct sensing of bisphenol A in real wine sample types without any pretreatment. The PDMS@SNCM/ITO electrode exhibit exceptional stability in alcoholic media. Abstract: Direct electrochemical analysis of bisphenol A (BPA) in alcoholic drinks without proper sample preparation is a major challenge. The current work reports a nanoporous electrode design with ultrathin polydimethylsiloxane (PDMS) coating grafted on the top of an indium tin oxide (ITO) electrode with silica nanochannels membrane and cetyltrimethylammonium bromide micelles (SNCM), using a facile contact heating step. The proposed PDMS@SNCM/ITO electrode was subjected to direct ultra-trace detection of BPA in the linear range of 1.0–100.0 µM and detection limit of 0.23 µM, under optimized pH 8 and an accumulation time of 9.0 min. The analytical utility of the proposed method was checked in real wine samples for BPA detection with successful recovery percentages in the range from 95.20 ± 8.53 to 96.22 ± 10.00. The intrinsic hydrophobic features, exceptional stability, and sensitivity of the proposed electrode show potential for food safety surveillance in complex food matrices.